Polymorphism of coagulase gene in Staphylococcus aureus isolated from buffaloe milk - J Shayegh; A.R Monadi (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2013)
The aim of this study was to analyze the coA gene on Staphylococcus aureus isolates collected from milks of native buffaloes in north-west of Iran. For this purpose, seventy five S. aureus isolates were examined by PCR-RFLP. Amplification of coA gene revealed various amplicons with a sizes of approximately 600, 700, 760 and 850 bp in 12, 25, 29 and 9 of the isolates, respectively. AluI digestion of the amplicons demonstrated that the isolates had the same PCR band size in the same PCR-RFLP patterns. The result of coA gen analysis was similar to the isolates from cattle milk.